2005
DOI: 10.1191/0269215505cr924oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home exercises on motor performance in patients with Parkinson's disease

Abstract: A home-based rehabilitation programme for patients with Parkinson's disease helped to improve motor performance compared to patients who did not take advantage of a regular, professionally designed exercise programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 15 publications
0
45
0
11
Order By: Relevance
“…This overall motor improvement may have acted as a confounder in the relationship between sensory cues and gait improvement. Prior studies have also shown nonpharmacological improvement in overall motor performance, such as home-based rehabilitation programs [29], and with other sensory stimulation, such as music [30]. This is also highlighted by the discrepancy often found during routine clinic assessments whereby patients perform better (e.g., less freezing) than what they report to experience in their homes, possibly because of the heightened attention and expectation during the increased scrutiny of clinic visits.…”
Section: Limitations Of This Studymentioning
confidence: 83%
“…This overall motor improvement may have acted as a confounder in the relationship between sensory cues and gait improvement. Prior studies have also shown nonpharmacological improvement in overall motor performance, such as home-based rehabilitation programs [29], and with other sensory stimulation, such as music [30]. This is also highlighted by the discrepancy often found during routine clinic assessments whereby patients perform better (e.g., less freezing) than what they report to experience in their homes, possibly because of the heightened attention and expectation during the increased scrutiny of clinic visits.…”
Section: Limitations Of This Studymentioning
confidence: 83%
“…While a previous exercise study also demonstrated improvements in 9HPT performance, that program included movement exercises for the upper extremities and hands. 49 As there are no specific hand movements practiced with tango dancing, we propose that improved 9HPT performance may be reflective of a global impact of exercise on bradykinesia. This is supported by the improvements in MDS-UPDRS-3 bradykinesia scores and is in keeping with the suggestion that participation in exercise may have disease modifying effects.…”
Section: Physical Functionmentioning
confidence: 99%
“…Os estudos divergem: Figueredo et al 17 optaram por reavaliar a adesão aos exercícios propostos a pacientes ambulatoriais submetidos à aplicação de toxina botulínica pós-trinta dias. Já Caglar et al 27 reavaliaram pacientes com doença de Parkinson após dois meses da instrução dos exercícios domiciliares. Esse último, no entanto, apresentou intuito diferente deste estudo, pois buscou avaliar a melhora funcional e não a adesão aos exercícios orientados.…”
Section: Discussionunclassified